Sun Exposure and Melanoma, Certainties and Weaknesses of the Present Knowledge - Arisi, Mariachiara; Zane, Cristina; Caravello, Simone; Rovati, Chiara; Zanca, Arianna; Venturini, Marina; Calzavara-Pinton, Piergiacomo (Frontiers in Medicine, 2018)
Sun exposure is the main risk factor for cutaneous malignant melanoma (CMM). However, the UV-related pathogenetic mechanisms leading to CMM are far to be fully elucidated. In this paper we will focus on what we still don’t fully know about the relationship between UVR and CMM. In particular, we will discuss: - The action spectrum of human CMM. - How different modalities of exposure (continuous/ intermittent; erythemal/ suberythemal) relate to different CMM variants. - The preferential UVR induced DNA mutations observed in different CMM variants. - The role of UV-related and UV- unrelated genetic damages in the same melanoma cells. - The importance of UVA induced oxidative and anaerobic damages to DNA and other cell structures. - The role of melanins. - The role of modulation of innate and acquired immunity. - The role of vitamin D. - The role of chronic exposure to phototoxic drugs and other xenobiotics A better understanding of these issues will help developing more effective preventative strategies and new therapeutic approaches.